"Palpably Ugly" or "beauty of their form"?: Corsets in Toronto periodicals, 1871-1914. (1st October 2020) - McKnight, Alanna
ABSTRACT: At the turn of the twentieth century in Toronto, articles in local newspapers and magazines exposed women to disparate views on corsets. On one side of the argument were dress reformers who advised women to do away with corsetry for the sake of their health and wellbeing. On the other side, were fashion journalists who advised them about current styles, which often oscillated from year-to-year. Despite this disparity, corsets were an ever-present foundation of nineteenth century fashion, to the extent that they were a frequent, sexy addition to crime reporting. The exaggerated stories in the media subjected women to a tug-of-war over their body autonomy. This article is based on content analyses of periodicals and exposes how corsets were presented in Toronto periodicals such as The Toronto Star, The Globe, and The Canadian Dried Goods Review, among others.